Clinical, hormonal and ovarian morphological correlation in women with polycystic ovary syndrome - Saini, Rishi R. S.; Gupta, Smirti; Tyagi, Mamta; Agrawal, Sachin; Gupta, Bharat K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Aim of the study was to study the correlation between clinical, ultrasonographical and hormonal features in women diagnosed as polycystic ovary syndrome (PCOS) and association with vitamin D levels. Methods: This prospective study was conducted among women attending gynecological outpatient department (OPD) of Subharti Medical College, Meerut over a period of two years among 100 patients with clinical diagnosis of PCOS/PCOD according to Rotterdam criteria (2013) were included in this study. All biochemical investigations to be carried out for levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), vitamin D levels, lipid profile to understand the endocrinal and metabolic derangements if any in the patient. Ultrasound pelvis for ovarian study was conducted to know the ovarian morphology, no of follicles if any and their size, which were helpful in the diagnosis of PCOS. Results: Nulliparity and multiparity was reported among 32% and 68% of the subjects respectively. Most common complaint was hirsuitism (43%). According to ultrasonography (USG), PCOS was found to be positive and negative among 87% and 13% of the subjects respectively. Most of the subjects had vitamin D level of 20-50 while <20 vitamin D level was found among 27% of the subjects. Vitamin D deficiency was found to be more in subjects having morphological presence of PCOS as compared to subjects with morphological absence of PCOS with statistically significant difference. Conclusions: On correlating ultrasonological findings with clinic hormonal changes in PCOS women we found that hirsuitism and vitamin d deficiency was significantly more common in women with sonological findings suggestive of PCOS.